Atrial arrhythmias in patients with arrhythmogenic right ventricular cardiomyopathy: Prevalence, echocardiographic predictors, and treatment. (24th July 2019) - Cardona‐Guarache, Ricardo; Åström‐Aneq, Meriam; Oesterle, Adam; Asirvatham, Roshini; Svetlichnaya, Jana; Marcus, Gregory M.; Gerstenfeld, Edward P.; Klein, Liviu; Scheinman, Melvin M.
Abstract: Introduction: The clinical role of atrial arrhythmias (AA) in arrhythmogenic right ventricular cardiomyopathy (ARVC) and the echocardiographic variables that predict them are not well defined. We describe the prevalence, types, echocardiographic predictors, and management of AA in patients with ARVC. Methods: We retrospectively evaluated medical records of 117 patients with definite ARVC (2010 Task Force Criteria) from two tertiary care centers. We identified those patients with sustained AA (>30 seconds), including atrial fibrillation (AF), atrial flutter (AFL), and atrial tachycardia (AT). We collected demographic, genetic, and clinical data. The median follow‐up was 3.4 years (interquartile range = 2.0‐5.7). Results: Total 26 patients (22%) had one or more types of AA: AF (n = 19), AFL (n = 9), and AT (n = 8). We performed genetic testing on 84 patients with ARVC (71.8%). Two patients with AA (8%) had peripheral emboli, and one patient (4%) suffered inappropriate implantable cardioverter‐defibrillator shock. We performed catheter ablation of AA in eight patients (31%), with no procedural complications. Right atrial area and left atrial volume index were independently associated with increased odds of AA; odds ratio (OR), 1.1 (95% confidence interval [CI]:1.02‐1.16) ( P  = .01) and OR, 1.1 (95% CI:1.03‐1.15) ( P  = .003), respectively. An increase in tricuspid annular plane peak systolic excursion was independently associated with reduced odds; OR, 0.3 (95% CI: 0.1‐0.94) ( P  = .003). Conclusions: Atrial arrhythmias (AA) are common in patients with arrhythmogenic right ventricular cardiomyopathy (ARVC). Inappropriate shocks and systemic emboli may be associated with AA. Atrial size and right ventricular dysfunction may help identify patients with ARVC at increased odds of AA.